2021
DOI: 10.1021/acs.orglett.1c01665
|View full text |Cite
|
Sign up to set email alerts
|

Aldehydes as Photoremovable Directing Groups: Synthesis of Pyrazoles by a Photocatalyzed [3+2] Cycloaddition/Norrish Type Fragmentation Sequence

Abstract: A straightforward methodology for the regioselective synthesis of pyrazoles has been developed by a domino sequence based on a photoclick cycloaddition followed by a photocatalyzed oxidative deformylation reaction. Distinguishing features of this protocol include an unprecedented photoredox-catalyzed Norrish type fragmentation under green-light irradiation and the use of α,β-unsaturated aldehydes as synthetic equivalents of alkynes, where the aldehyde is acting as a novel photoremovable directing group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…The structure design of novel styrylpyrazoles is possible via the functionalization of a heterocycle, as well as via its reassociation with the substrate and reactant containing the desired substituents. 3,4 The first group of methods mostly includes cross-coupling (Suzuki–Miyaura, Mizoroki–Heck) reactions allowing the formation of a connection with the vinyl fragment, 12 c ,13 along with the transformation of tetrazole-type heterocycles 14 and some other methodologies. 11 d The second group is represented by 1,3-dipolar cycloaddition to α,β-unsaturated carbonyl compounds 15 and various cyclocondensation reactions of hydrazines and substituted hydrazines with 1,3-diketones, 5 e,j , k , m – o ,9,10,11 c,e dienones and their synthetic equivalents 4,12 d ,14,16 (see the review by Gomes and coworkers 4 for details).…”
Section: Introductionmentioning
confidence: 99%
“…The structure design of novel styrylpyrazoles is possible via the functionalization of a heterocycle, as well as via its reassociation with the substrate and reactant containing the desired substituents. 3,4 The first group of methods mostly includes cross-coupling (Suzuki–Miyaura, Mizoroki–Heck) reactions allowing the formation of a connection with the vinyl fragment, 12 c ,13 along with the transformation of tetrazole-type heterocycles 14 and some other methodologies. 11 d The second group is represented by 1,3-dipolar cycloaddition to α,β-unsaturated carbonyl compounds 15 and various cyclocondensation reactions of hydrazines and substituted hydrazines with 1,3-diketones, 5 e,j , k , m – o ,9,10,11 c,e dienones and their synthetic equivalents 4,12 d ,14,16 (see the review by Gomes and coworkers 4 for details).…”
Section: Introductionmentioning
confidence: 99%
“…S22†). All these results suggest that a reductive quenching photocatalytic cycle of eosin Y 33,34 might be merged with electrocatalysis.…”
Section: Resultsmentioning
confidence: 84%
“…Eosin Y is a versatile photosensitizer, 31 and while it is a frequently used photoreductant, 32 it could function as a photooxidant as well. 33,34 Cyclic voltammetry (CV) tests indicated that eosin Y has an oxidation potential of 1.00 V vs. Ag/AgCl (Scheme 3d and Fig. S9–S11†).…”
Section: Resultsmentioning
confidence: 99%
“…[5] Furthermore, these scaffolds have been extensively employed as ligands in transition metal-catalyzed reactions, precursors to N-heterocyclic carbenes (NHCs) and polymer chemistry. [6] The classical approaches for the synthesis of pyrazoles involve the condensation reaction of 1,3-dicarbonyls with hydrazine derivatives and 1,3-dipolar cycloaddition reaction of diazo compounds with alkynes that have own merits and demerits. [7] Owing to their significant value, the development of efficient and novel strategies for the preparation of pyrazole backbone and its derivatives is an attractive research topic in medicinal chemistry and organic synthesis.…”
mentioning
confidence: 99%